2017
DOI: 10.1038/pr.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Bach1 gene enhances recovery from hyperoxic lung injury in newborn mice via transient upregulation of inflammatory genes

Abstract: Bach1 newborn mice were well-recovered from hyperoxia-induced lung injury. This effect is likely achieved by the antioxidant/anti-inflammatory activity of HO-1 or by the transient overexpression of proinflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(39 reference statements)
0
19
2
Order By: Relevance
“…While Nrf2 induces the expression of HO-1, Bach1, a leucin zipper protein, is a physiological repressor of HO-1 [95]. The effects of silencing Bach1 in a mouse model of hyperoxic lung injury has been recently studied [96,97]. Go et al [97] demonstrated that under physiological conditions, miR-196a is able to silence Bach1 giving rise to an increase in lung HO-1 expression, whereas under hyperoxic stress miR-196a is degraded with a consequent reduction in HO-1 levels.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 99%
See 1 more Smart Citation
“…While Nrf2 induces the expression of HO-1, Bach1, a leucin zipper protein, is a physiological repressor of HO-1 [95]. The effects of silencing Bach1 in a mouse model of hyperoxic lung injury has been recently studied [96,97]. Go et al [97] demonstrated that under physiological conditions, miR-196a is able to silence Bach1 giving rise to an increase in lung HO-1 expression, whereas under hyperoxic stress miR-196a is degraded with a consequent reduction in HO-1 levels.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 99%
“…Go et al [97] demonstrated that under physiological conditions, miR-196a is able to silence Bach1 giving rise to an increase in lung HO-1 expression, whereas under hyperoxic stress miR-196a is degraded with a consequent reduction in HO-1 levels. Ito et al [96] developed a mouse model of Bach1 −/− which demonstrated improved alveolarization after 4 days neonatal hyperoxic exposure (21 or 95% oxygen) and room air recovery. After assessing lung histology and measuring mRNA levels of lung Bach1, HO-1, interleukin (IL)-6 (IL-6), and monocyte chemoattractant protein (MCP)-1 it was observed a significant increment in HO-1, IL-6, and (MCP)-1 mRNA levels.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 99%
“…We hypothesized that BACH1 might regulate ferroptosis by inhibiting the expression of these genes. In addition, since BACH1 is involved in the exacerbation of various diseases involving oxidative stress, such as ischemic heart disease (Yano et al, 2006), hyperoxic lung injury (Ito et al, 2017), trinitrobenzene sulfonic acid-induced colitis (Harusato et al, 2013), nonalcoholic steatohepatitis (Inoue et al, 2011), and spinal cord injury (Kanno et al, 2009), BACH1 may exacerbate the severity of these diseases through ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to oxidative stresses results in the dissociation of Keap1 from Nrf2, therefore Nrf2 translocate to the nucleus and binds to the ARE sequence of several cytoprotective genes to induce transcription, including HO‐1 gene . BTB and CNC homology 1 (Bach1) is a transcriptional repressor of HO‐1, and the antioxidant effect of HO‐1 is enhanced in Bach1 deficiency mice . In addition, it is reported that Bach1 can competitively bind to ARE‐like enhancer of HO‐1 to antagonize Nrf2 binding in cells unexposed to oxidative damage …”
Section: Introductionmentioning
confidence: 99%
“…17 BTB and CNC homology 1 (Bach1) is a transcriptional repressor of HO-1, 18,19 and the antioxidant effect of HO-1 is enhanced in Bach1 deficiency mice. 20,21 In addition, it is reported that Bach1 can competitively bind to ARE-like enhancer of HO-1 to antagonize Nrf2 binding in cells unexposed to oxidative damage. 22 In the present article, we explored the roles of HO-1 pathway and the regulatory mechanisms of this pathway using HO-1 inducer cobalt protoporphyrin (Copp) and HO-1 inhibitor zinc protoporphyrin (Znpp) in lung injury following LIR in rats.…”
mentioning
confidence: 99%